Titanium nitride doped fluoride-free photo-thermal super-hydrophobic coating as well as preparation method and application thereof
A TiN doped, fluorine-free photothermal superhydrophobic coating addresses the inefficiencies and environmental hazards of existing anti-icing methods by using LSPR nanoparticles to convert sunlight into heat for efficient ice prevention and removal, ensuring sustainability and durability.
Patent Information
- Application Number
- CN202510465975.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2025-07-15
AI Technical Summary
The biotoxicity of fluoride-containing compounds in existing superhydrophobic coating materials and the harm to ecological balance. The traditional deicing strategy is inefficient and costly, making it difficult to achieve environmentally friendly and efficient anti-icing effects.
A fluorine-free photothermal superhydrophobic coating doped with titanium nitride (TiN) nanoparticles is used to construct a micro-nano hierarchical structure through the combination of polydimethylsiloxane-modified TiN nanoparticles and hydrophobic nanoparticles and adhesives, and utilize local surface plasmon resonance and photothermal effects to achieve efficient waterproofing and ice-repellency.
Quickly remove frost in low temperature environments, delay icing, self-cleaning, anti-icing and deicing functions, use renewable solar energy to green and environmentally friendly, suitable for complex and extreme environments, and the preparation method is simple and easy to industrialize.
Smart Images

Figure CN120310370A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional coating materials, and particularly relates to a titanium nitride-doped fluorine-free photothermal superhydrophobic coating, a preparation method thereof, and an application thereof. Background Art
[0002] The icing phenomenon in nature brings great troubles to people's daily lives. For example, icing on aircraft wings can lead to a reduction in flight speed and even cause serious air disasters. Icing on transmission lines easily causes electrical short circuits. These icing phenomena not only increase energy consumption but also pose a threat to human safety. The traditional strategies to solve these problems mainly include mechanical vibration, chemical anti-icing agents, and electrothermal de-icing, but these strategies are inefficient, costly, and harmful to the environment. Therefore, people have spent a lot of energy developing green and energy-saving anti / de-icing materials. Superhydrophobic surfaces provide an effective method for delaying icing. This is based on the presence of an air layer within the surface structure, which can greatly reduce the contact area between water droplets and the solid substrate. Introducing photothermal materials into superhydrophobic coatings can effectively convert solar energy into heat energy, promote the melting of ice at the interface, and then remove the un-melted ice through low surface energy and superhydrophobicity. Currently, researchers usually use low-surface-energy fluorinated particles or fluorine-containing polymers to obtain excellent superhydrophobicity, but they ignore the biological toxicity of fluorides and the harm to the ecological balance. For example, fluorinated chemicals are not easily decomposed and accumulate in water sources, soil, and organisms, and are known as "forever chemicals", ultimately threatening the survival and development of humans. Therefore, preparing an environmentally friendly fluorine-free and superhydrophobic coating material with stable ice-phobic performance is an important trend for maintaining sustainable development in the anti / de-icing field.
[0003] Nanoparticles based on the localized surface plasmon resonance effect (LSPR) are common photothermal materials in the fields of phototherapy and catalysis. It generates hot carriers through Landau damping, interacts with phonons, converts energy into the vibrational energy of the lattice, and transfers it to the surrounding environment to increase the temperature. Considering the high cost of precious metals such as gold and silver and their narrow spectral absorption bands, recent studies have shown that plasma materials based on cermets can be used as substitutes for photothermal conversion in the visible and near-infrared regions. Among them, the most typical material is titanium nitride (TiN) nanoparticles. TiN has significant advantages, such as having a wide adsorption wavelength in both the visible and near-infrared regions, good corrosion resistance stability, high melting point, high hardness, and affordable price. To sum up, doping TiN into a superhydrophobic coating as a photothermal absorber has a wide absorption in the visible and near-infrared regions and converts it into heat energy, inhibiting icing on the coating surface and melting and removing frost, with the significant advantages of environmental protection, energy saving, high efficiency, and simplicity. Summary of the Invention
[0004] (I) Technical Problems to be Solved
[0005] The present invention provides a titanium nitride-doped fluorine-free photothermal superhydrophobic coating, a preparation method thereof and an application thereof, so as to solve the technical problem of how to achieve efficient waterproofing and ice-phobicity.
[0006] (II) Technical solution
[0007] To solve the above technical problem, the present invention provides a preparation method of a titanium nitride-doped fluorine-free photothermal superhydrophobic coating. The preparation method of the photothermal superhydrophobic coating comprises the following steps:
[0008] S1. Ultrasonically disperse polydimethylsiloxane-modified titanium nitride PDMS-TiN, hydrophobic nanoparticles and an adhesive in an organic solvent to obtain a coating solution;
[0009] S2. Perform surface finishing and cleaning treatment on a substrate; spray or scrape the coating solution on the surface of the substrate and heat for curing to obtain a titanium nitride-doped fluorine-free photothermal superhydrophobic coating.
[0010] Further, PDMS-TiN is polydimethylsiloxane-modified TiN nanoparticles, which are obtained by modifying acid-hydrolyzed TiN nanoparticles with asymmetric monoaminopropyl polydimethylsiloxane NH2-PDMS.
[0011] Further, in step S1, the preparation of PDMS-TiN specifically comprises the following steps:
[0012] S1-1. Disperse TiN nanoparticles in ethanol, add a silane coupling agent KH-560 and water, adjust the pH value by adding acetic acid, perform an acidolysis reaction, and after centrifugation, ethanol washing and drying, obtain acid-hydrolyzed TiN nanoparticles;
[0013] S1-2. Mix the acid-hydrolyzed TiN nanoparticles and an organic solvent, add NH2-PDMS for graft modification, and dry to obtain PDMS-TiN.
[0014] Further, in step S1-1, the mass ratio of TiN, KH-560, ethanol, acetic acid and water is (2-3):(4-2.0):(4-6):(18-25):(0.4-0.8):2; in step S1-2, the mass ratio of the acid-hydrolyzed TiN nanoparticles, NH2-PDMS and the organic solvent is (0.5-1):(0.5-1.2):10; the average molecular weight of NH2-PDMS is 1500-2500 g / mol.
[0015] Further, in step S1-1, the size of the TiN nanoparticles is 20-50 nm; acetic acid is used to adjust the pH value to 4-5; the acidolysis reaction temperature is 60 °C, and the reaction time is 2-3 h; the rotation speed of the centrifugation operation is 5000-10000 rpm, and the drying temperature is 60-80 °C; in S1-2, the graft modification reaction temperature is 70-80 °C, the reaction time is 1.5-3 h, and the drying temperature is 80-100 °C.
[0016] Further, the adhesive is selected from one or more of polyurethane, epoxy resin, and polyacrylic resin; the hydrophobic nanoparticles are selected from one or two of silicon dioxide and silicon carbide; the organic solvent is selected from one or more of methyl ethyl ketone, butyl acetate, and ethyl acetate; in step S1, the mass ratio of PDMS-TiN, hydrophobic nanoparticles, adhesive, and organic solvent is (0.05-0.25):(0.2-0.3):(0.4-0.6):5.
[0017] Further, in step S1, the ultrasonic power is 200±50 W, and the ultrasonic time is 5-10 min.
[0018] Further, in step S2, the substrate is iron, copper, aluminum, steel, or glass. The surface of the substrate is finish-machined with sandpaper or cotton cloth, and then ultrasonically cleaned in anhydrous ethanol and deionized water in sequence and dried; for spraying, a spray gun with a nozzle diameter of 2.5±0.5 mm is used, the compressed air pressure is 0.8-1.0 MPa, the working distance between the substrate and the spray gun is 15-20 cm, the heating and curing temperature is 100-120 °C, and the curing time is 10-30 min.
[0019] In addition, the present invention also provides a titanium nitride-doped fluorine-free photothermal superhydrophobic coating prepared by the above method. The water contact angle of the titanium nitride-doped fluorine-free photothermal superhydrophobic coating is 155-162°; the water droplet rolling angle is 3±1°; under the irradiation of 1 solar light intensity and an environmental temperature of -30 °C, the ice formation delay time is greater than 30 min, and the defrosting time is 32±3 s.
[0020] In addition, the present invention also provides an application of the above titanium nitride-doped fluorine-free photothermal superhydrophobic coating. The titanium nitride-doped fluorine-free photothermal superhydrophobic coating is used for waterproofing and ice-phobicity on the surfaces of electronic components and structural parts.
[0021] (III) Beneficial effects
[0022] The present invention provides a fluorine-free photothermal superhydrophobic coating doped with titanium nitride, a preparation method thereof and an application thereof. The raw materials of the fluorine-free photothermal superhydrophobic coating material doped with titanium nitride include polydimethylsiloxane-modified titanium nitride, hydrophobic nanoparticles and an adhesive. It has excellent local surface plasmon resonance effect and photothermal effect. At the same time, the coating has a rough and uniform micro-nano hierarchical structure, which can efficiently remove dynamic water and delay icing. In an environment of -30 °C, the surface temperature can reach 12 °C only under the irradiation of one sunlight intensity, and rapid de-icing can be achieved. The coating has good functions such as self-cleaning, anti-icing, de-icing and defrosting, utilizes renewable solar energy, is green, environmentally friendly, energy-saving and emission-reducing. At the same time, the superhydrophobic surface of the coating can effectively delay icing and inhibit ice adhesion. Based on the synergistic effect of superhydrophobicity and photothermal effect, the coating realizes the organic combination of active de-icing and passive de-icing strategies.
[0023] The beneficial effects of the present invention specifically include:
[0024] (1) The acid-hydrolyzed TiN nanoparticles are graft-modified with polydimethylsiloxane, which not only ensures its photothermal performance, but also endows it with excellent antioxidant and hydrophobic properties.
[0025] (2) The coating has a micro-nano hierarchical structure and a low surface energy surface. The rough surface can capture air to form a "gas cushion", reduce the contact area between the liquid and the surface, increase the slipperiness of the liquid droplets, and thus obtain an excellent superhydrophobic surface, which can quickly remove the surface ice and inhibit icing at low temperatures (such as -30 °C).
[0026] (3) Under the irradiation of sunlight in the full wavelength range, the coating realizes the collection and absorption of light through multiple reflections, and the LSPR effect of TiN can enhance the photothermal effect and accelerate de-icing.
[0027] (4) The coating has durability and mechanical-chemical stability. It can still maintain superhydrophobic performance under conditions such as immersion in corrosive solutions, high and low temperature cycling, long-term ultraviolet irradiation, multiple sand impacts, multiple sandpaper abrasions and repeated tape peeling, and is suitable for functional applications in complex and extreme environments.
[0028] (5) The preparation method of the present invention has simple operation steps, low cost, universality, and is easy to industrialize. Description of the Drawings
[0029] Figure 1 It is a graph of the superhydrophobic performance of the fluorine-free photothermal superhydrophobic coating doped with titanium nitride in the embodiment of the present invention;
[0030] Figure 2 It is a surface micrograph of the fluorine-free photothermal superhydrophobic coating doped with titanium nitride in Example 2 of the present invention;
[0031] Figure 3Photothermal absorption performance diagram of the titanium nitride-doped fluorine-free photothermal superhydrophobic coating in the embodiment of the present invention;
[0032] Figure 4 Photothermal conversion performance diagram of the titanium nitride-doped fluorine-free photothermal superhydrophobic coating in Example 2 of the present invention;
[0033] Figure 5 De / anti-icing performance diagram of the titanium nitride-doped fluorine-free photothermal superhydrophobic coating in the embodiment of the present invention. Specific embodiments
[0034] To make the objectives, contents, and advantages of the present invention clearer, the following further describes in detail the specific embodiments of the present invention with reference to the drawings and examples.
[0035] One sun intensity is a standard value used to simulate solar illumination conditions, which refers to the solar irradiance received perpendicular to the sunlight direction at noon on a sunny day on the earth's surface. Specifically, it is 1000 watts per square meter (1000 W / m 2 ).
[0036] Example 1
[0037] (1) Disperse 3 g of TiN in 22 mL of ethanol, add 4 g of KH-560 and 2 mL of water, adjust the pH value to 4 with acetic acid, and react at 60 °C for 2 h. After centrifugation at 5000 rpm and washing with ethanol three times, dry at 60 °C to obtain acid-hydrolyzed TiN nanoparticles; Disperse 0.50 g of acid-hydrolyzed TiN nanoparticles in 10 g of methyl ethyl ketone, then add 0.50 g of NH2-PDMS and react at 70 °C for 2 h, and dry at 80 °C to obtain polydimethylsiloxane-modified titanium nitride nanoparticles (PDMS-TiN).
[0038] (2) Disperse 0.25 g of hydrophobic SiO2 nanoparticles and 0.05 g of PDMS-TiN in 5 g of butyl acetate at room temperature, ultrasonically treat for 10 minutes, and add 0.4 g of epoxy resin and stir to mix evenly to obtain a coating solution.
[0039] (3) Prepare a glass substrate, perform finishing on the surface with a cotton cloth, and then ultrasonically clean it in anhydrous ethanol and deionized water in turn, each cleaning for 10 minutes, and dry it for later use.
[0040] (4) Spray the coating solution evenly on the glass substrate. The spray gun uses a nozzle with a diameter of about 2.5 mm, the compressed air pressure is 0.8 MPa, and the working distance between the substrate and the spray gun is 15 cm. Cure at 110 °C for 10 minutes to obtain a titanium nitride-doped fluorine-free photothermal superhydrophobic coating.
[0041] Example 2
[0042] (1) Disperse 2.5 g of TiN in 20 mL of ethanol, add 4 g of KH-560 and 2 mL of water, adjust the pH value to 5 with acetic acid, and react at 60 °C for 2 h. After centrifugation at 5000 rpm and washing with ethanol three times, dry at 60 °C to obtain acid-hydrolyzed TiN nanoparticles; disperse 1.0 g of acid-hydrolyzed TiN nanoparticles in 10 g of ethyl acetate, then add 1.2 g of NH2-PDMS and react at 70 °C for 2.5 h, and dry at 80 °C to obtain polydimethylsiloxane-modified titanium nitride nanoparticles (PDMS-TiN).
[0043] (2) Disperse 0.30 g of hydrophobic SiO2 nanoparticles and 0.15 g of PDMS-TiN in 5 g of a mixed solvent (m 丁酮 / m 乙酸丁酯 = 1) at room temperature, ultrasonically treat for 20 minutes, add 0.5 g of polyurethane and stir to mix evenly to obtain a coating solution.
[0044] (3) Prepare a copper sheet substrate, perform finishing on the surface with sandpaper, and then ultrasonically clean in absolute ethanol and deionized water in turn, each cleaning for 15 minutes, and dry for later use.
[0045] (4) Spray the coating solution evenly on the copper sheet substrate. The spray gun uses a nozzle with a diameter of about 3.0 mm, the compressed air pressure is 0.9 MPa, and the working distance between the substrate and the spray gun is 20 cm. Cure at 110 °C for 20 minutes to obtain a fluorine-free photothermal superhydrophobic coating doped with titanium nitride.
[0046] Example 3
[0047] (1) Disperse 2.0 g of TiN in 20 mL of ethanol, add 3.5 g of KH-560 and 2 mL of water, adjust the pH value to 5 with acetic acid, and react at 60 °C for 3 h. After centrifugation at 5000 rpm and washing with ethanol three times, dry at 60 °C to obtain acid-hydrolyzed TiN nanoparticles; disperse 0.7 g of acid-hydrolyzed TiN nanoparticles in 10 g of butyl acetate, then add 1.0 g of NH2-PDMS and react at 80 °C for 3 h, and dry at 90 °C to obtain polydimethylsiloxane-modified titanium nitride nanoparticles (PDMS-TiN).
[0048] (2) Disperse 0.25 g of hydrophobic SiC nanoparticles and 0.25 g of PDMS-TiN in 5 g of butyl acetate at room temperature, ultrasonically treat for 10 minutes, add 0.5 g of polyacrylic resin and stir to mix evenly to obtain a coating solution.
[0049] (3) Prepare an aluminum sheet substrate, perform finishing on the surface with sandpaper, and then ultrasonically clean in absolute ethanol and deionized water in turn, each cleaning for 15 minutes, and dry for later use.
[0050] (4) The coating liquid was evenly sprayed onto the aluminum substrate. The spray gun used a nozzle with a diameter of about 2.5 mm, the compressed air pressure was 0.9 MPa, and the working distance between the substrate and the spray gun was 20 cm. After curing at 100 °C for 30 minutes, a titanium nitride-doped fluorine-free photothermal superhydrophobic coating was obtained.
[0051] Performance test
[0052] Freezing cycle experiment: The water contact angle and rolling angle of the coatings prepared in Examples 1 to 3 were measured using a contact angle meter, and the freezing / de-icing experiments were carried out under the conditions of -20 °C and 1.0 sun photothermal. The test results of the coatings are shown as follows:
[0053] Figure 1 For the demonstration of the superhydrophobic performance of the titanium nitride-doped fluorine-free photothermal superhydrophobic coatings described in Examples 1 to 3. From Figure 1 It can be seen that the water contact angle of the coating prepared in Example 2 is 158°, and the water contact angles of the coatings prepared in Examples 2 and 3 are also higher than 155°. At the same time, the water droplet rolling angle of the coating is only 3-5°, showing good superhydrophobicity.
[0054] Figure 2 For the demonstration of the surface microstructure of the titanium nitride-doped fluorine-free photothermal superhydrophobic coating prepared in Example 2. As Figure 2 shown in (a) of, many "tower-shaped" protruding rough structures are evenly distributed on the coating surface. Figure 2 When magnified to 1000 times in (b) of, it can be clearly seen that the nanoparticles are wrapped and fixed on the surface, and there are a large number of voids between them. Especially in (c) magnified 50,000 times of Figure 2 PDMS-TiN and hydrophobic nanoparticles are adhered and piled up into an irregular hierarchical structure, and there are a large number of voids between the tower-shaped aggregates. These voids provide sufficient space for trapping air, thus endowing the coating with high superhydrophobicity.
[0055] Figure 3 For the demonstration of the light absorption performance of the titanium nitride-doped fluorine-free photothermal superhydrophobic coatings prepared in Examples 1 to 3. Figure 3 In (a) of, it can be observed that the reflectivity of the coating to incident light in the wavelength range of 200-2500 nm is basically within 5%. This low reflectivity is due to the micro-nano hierarchical structure on the coating surface and the LSPR effect of titanium nitride. The incident light is multiply reflected, trapped and absorbed on the surface. Figure 3 In (b) of, it can be clearly shown that the absorption rate of the coating to incident light exceeds 95%, providing good guarantee for the photothermal performance of the coating.
[0056] Figure 4 For the demonstration of the photothermal conversion performance of the titanium nitride-doped fluorine-free photothermal superhydrophobic coating prepared in Example 1. As Figure 4As shown in (a), in an environment of 25°C and 1 sun intensity, when the coating is exposed to light, the surface temperature changes rapidly and can reach the highest equilibrium temperature within 10 minutes, with the surface temperature reaching 67°C; as Figure 4 shown in (b), in an environment of -30°C and 1 sun intensity, the highest equilibrium temperature can be reached within 10 minutes, which is 12°C. This coating exhibits excellent photothermal effects, which is beneficial for improving its anti-icing performance and delaying ice formation in low-temperature environments.
[0057] Figure 5 This is the demonstration of the anti- / de-icing performance of the fluorine-free photothermal superhydrophobic coating doped with titanium nitride prepared in Example 1. As Figure 5 shown, under 1 sun illumination at -20°C, the droplet delay icing time on the coating exceeds 60 minutes, and on the already-iced surface, the ice on the surface can be melted and removed with just under 3 minutes of illumination, showing good anti-icing performance.
[0058] In the present invention, PDMS-TiN, hydrophobic nanoparticles, and an adhesive form a superhydrophobic surface with a lotus effect. The incident light is fully absorbed through the LSPR effect and multiple reflections, which also enhances the photothermal conversion of the coating. PDMS-TiN itself has the LSPR effect and a high photothermal conversion rate. At the same time, asymmetric monoaminopropyl polydimethylsiloxane and silane coupling agent can effectively bind and encapsulate TiN, which can enhance its hydrophobicity and antioxidant ability, regulate the dispersion of PDMS-TiN in organic media, and mitigate the interfacial mismatch with the polymer matrix. The synergistic effect of the superhydrophobic surface and photothermal conversion helps the material to efficiently prevent and remove ice in low-temperature and high-humidity environments.
[0059] The hydrophobic nanoparticles and PDMS-TiN can construct a superhydrophobic surface with a low surface energy and roughness. The micro-nano structure on the surface will capture a large number of air cavities under the droplet, forming a thermal barrier, which can passively remove dynamic water and delay the accumulation of ice. The presence of the adhesive helps to protect and strengthen the stability of the filled particles in the coating and the firmness of the substrate. The present invention can obtain a physically and chemically stable fluorine-free photothermal superhydrophobic coating doped with titanium nitride. The photothermal superhydrophobic coating material provided by the present invention can solve the problem of deteriorated hydrophobic stability of traditional superhydrophobic coatings caused by low temperature or high humidity. The synergistic effect of the LSPR effect of titanium nitride and the micro / nano hierarchical structure enables the superhydrophobic coating to have excellent light absorption and photothermal conversion capabilities, which helps to maintain the superhydrophobic state and accelerate the de-icing process, achieving efficient and stable anti-icing / de-icing performance.
[0060] The present invention adopts the strategy of "adhesive + coating", and is a composite prepared from polydimethylsiloxane-modified titanium nitride (PDMS-TiN) nanoparticles, hydrophobic nanoparticles and an adhesive; among them, PDMS-TiN is a hydrophobic TiN nanoparticle modified by asymmetric monoaminopropyl polydimethylsiloxane, which has excellent antioxidant properties and photothermal effects; PDMS-TiN and hydrophobic nanoparticles can construct a superhydrophobic surface with a lotus effect. In particular, the grafted polydimethylsiloxane chains can reduce the surface energy of the coating and provide a molecular lubricating layer similar to a liquid to reduce the adhesion of liquids and ice on the surface. The water contact angle is above 155°, and the water droplet rolling angle is below 5°; at the same time, the LSPR effect of titanium nitride can increase the capture and absorption of light by the rough surface; the titanium nitride-doped fluorine-free photothermal superhydrophobic coating material can effectively delay the icing time by more than 30 minutes under a low-temperature environment of -30°C with only the irradiation of one sunlight intensity. Especially in terms of defrosting, it can be completely removed in only 32 seconds; the titanium nitride-doped fluorine-free photothermal superhydrophobic coating prepared by the present invention can significantly enhance the anti-icing and de-icing performance of the surface, and utilizes green and renewable solar renewable light energy, meeting the development needs of clean production and low-carbon economy.
[0061] The PDMS-TiN nanoparticles prepared by the present invention through optimizing the preparation process of PDMS-TiN have excellent hydrophobic properties, antioxidant properties and photothermal conversion efficiency, and can improve the overall performance of the coating. By controlling parameters such as the dosage ratio, reaction time and temperature, and further optimizing the modification conditions of the PDMS-TiN nanoparticles, the performance of the coating material can be further improved.
[0062] The coating prepared by the present invention can be specifically applied to the electronic components and / or structural parts in the fields of aviation, ocean engineering, power industry and / or aerospace that work in cold environments, and can especially be applied to the waterproofing and ice shedding of the electronic components and / or structural parts on the surfaces of airplanes, wind turbines, transmission lines, outdoor electronic products used in cold regions, ships and offshore operation platforms.
[0063] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the technical principle of the present invention, several improvements and deformations can still be made, and these improvements and deformations should also be regarded as the protection scope of the present invention.
Claims
1. A preparation method of a titanium nitride-doped fluorine-free photothermal superhydrophobic coating, characterized in that, The method for preparing the photothermal superhydrophobic coating comprises the following steps: S1. PDMS-TiN modified by polydimethylsiloxane, hydrophobic nanoparticles and an adhesive are ultrasonically dispersed into an organic solvent to obtain a coating solution; S2. The substrate is subjected to surface finishing and cleaning treatment; the coating solution is sprayed or scraped on the surface of the substrate and heated for curing to obtain a fluorine-free photothermal superhydrophobic coating doped with titanium nitride.
2. The method for preparing a titanium nitride-doped fluorine-free photothermal superhydrophobic coating according to claim 1, wherein PDMS-TiN is TiN nanoparticles modified by polydimethylsiloxane, and is obtained by modifying acid-hydrolyzed TiN nanoparticles with asymmetric monoaminopropyl polydimethylsiloxane NH2-PDMS.
3. The preparation method of the titanium nitride-doped fluorine-free photothermal superhydrophobic coating according to claim 1, characterized in that, In step S1, the preparation of PDMS-TiN specifically comprises the following steps: S1-1. TiN nanoparticles are dispersed in ethanol, silane coupling agent KH-560 and water are added, the pH value is adjusted by adding acetic acid, an acid hydrolysis reaction is carried out, and after centrifugation, ethanol washing and drying, acid-hydrolyzed TiN nanoparticles are obtained; S1-2. The acid-hydrolyzed TiN nanoparticles and an organic solvent are mixed, NH2-PDMS is added for grafting modification, and after drying, PDMS-TiN is obtained.
4. The method for preparing a titanium nitride-doped fluorine-free photothermal superhydrophobic coating according to claim 3, characterized in that, In step S1-1, the mass ratio of TiN, KH-560, ethanol, acetic acid and water is (2-3):(4-2.0):(4-6):(18-25):(0.4-0.8):2; in step S1-2, the mass ratio of acid-hydrolyzed TiN nanoparticles, NH2-PDMS and an organic solvent is (0.5-1):(0.5-1.2):10; the average molecular weight of NH2-PDMS is 1500-2500 g / mol.
5. The method for preparing a titanium nitride-doped fluorine-free photothermal superhydrophobic coating according to claim 3, wherein, In step S1-1, the size of the TiN nanoparticles is 20-50 nm; the pH value adjusted by acetic acid is 4-5; the temperature of the acid hydrolysis reaction is 60 °C, and the reaction time is 2-3 h; the rotation speed of the centrifugation operation is 5000-10000 rpm, and the drying temperature is 60-80 °C; in S1-2, the temperature of the grafting modification reaction is 70-80 °C, the reaction time is 1.5-3 h, and the drying temperature is 80-100 °C.
6. The method for preparing a titanium nitride-doped fluorine-free photothermal superhydrophobic coating according to claim 1, wherein, The adhesive is selected from one or more of polyurethane, epoxy resin and polyacrylic resin; the hydrophobic nanoparticles are selected from one or two of silicon dioxide and silicon carbide; the organic solvent is selected from one or more of methyl ethyl ketone, butyl acetate and ethyl acetate; in step S1, the mass ratio of PDMS-TiN, hydrophobic nanoparticles, adhesive and organic solvent is (0.05-0.25):(0.2-0.3):(0.4-0.6):
5.
7. The preparation method of the titanium nitride-doped fluorine-free photothermal superhydrophobic coating according to claim 1, characterized in that, In step S1, the ultrasonic power is 200±50 W, and the ultrasonic time is 5-10 min.
8. The method for preparing a titanium nitride-doped fluorine-free photothermal superhydrophobic coating according to claim 1, wherein In step S2, the substrate is iron, copper, aluminum, steel or glass. The surface of the substrate is subjected to finishing by sandpaper or cotton cloth, and then ultrasonically cleaned in anhydrous ethanol and deionized water in sequence and dried; for spraying, a spray gun with a nozzle diameter of 2.5±0.5 mm is used, the compressed air pressure is 0.8-1.0 MPa, the working distance between the substrate and the spray gun is 15-20 cm, the heating and curing temperature is 100-120 °C, and the curing time is 10-30 min.
9. A titanium nitride-doped fluorine-free photothermal superhydrophobic coating, characterized in that, Prepared by the method according to any one of claims 1 to 8, the water contact angle of the titanium nitride-doped fluorine-free photothermal superhydrophobic coating is 155-162°; the water droplet rolling angle is 3±1°; under the irradiation of 1 sun intensity and an ambient temperature of -30°C, the ice formation delay time is greater than 30 min, and the defrosting time is 32±3 s.
10. Use of a titanium nitride-doped fluorine-free photothermal superhydrophobic coating as described in claim 9, characterized in that, The titanium nitride-doped fluorine-free photothermal superhydrophobic coating is used for waterproofing and ice-phobicity on the surfaces of electronic components and structural components.
Citation Information
Cited By
Fluorine-free super-hydrophobic silicon dioxide / titanium nitride coating, method and application thereof
CN121406212A
Multifunctional composite coating of OSB (oriented strand board) and preparation method of multifunctional composite coating
CN121537883A
A multifunctional composite coating for OSB substrate and its preparation method
CN121537883B